Suspension of social welfare services and mental health outcomes for women during the COVID-19 pandemic in a peripheral neighborhood in São Paulo, Brazil - Bruhn, Lenora; Szabzon, Felipe; Abarca Brown, Cristobal; Ravelli Cabrini, Daniela; Miranda, Elisangela; Andrade, Laura Helena (Frontiers in Psychiatry, 2022)
During the COVID-19 pandemic, Brazilian urban peripheries have been severely affected both by the spread of the virus and by social, political, and economical dynamics, raising concerns about the psychological wellbeing and mental health of the population living in these areas. The pandemic broke out in a context of reduced public spending in social and health policies as well as in a process of erosion of social rights, fostering processes of exclusion and highlighting the association between austerity, the increase in poverty and inequality as well as in health and mental health problems indicators. This article presents the results of a qualitative participatory research that investigated subjective experiences in a peripheral neighborhood of São Paulo, Brazil, aiming to understand how contextual dynamics played a role in shaping mental health experiences during the COVID-19 pandemic. A multidisciplinary team of researchers worked closely with local volunteers trained to provide emotional support calls to neighbors of the community who signed up for the project. This article presents three ethnographic cases of women who had their routines strongly affected by the suspension of public and social protection services for the containment of the SARS-CoV-2 pandemic, leading to psychological suffering due to the increased demand of “domestic circuits of care”. We argue that within a context of austerity, the pandemic was remarkably harsh in urban peripheries and, specifically, for women with caring responsibilities. In addition to highlighting the pervasive “social protection gap”, the cases presented in this paper also reveals the unequal dynamics of the social reproduction work in several layers, which falls mainly on women's shoulders. The “crisis of care”, proposed by gender and feminist scholars, can contribute to understanding the psychological outcomes of the COVID-19 pandemic for these women.